2006
DOI: 10.1161/01.atv.0000201932.32678.7e
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Contributes to Endothelial Dysfunction in Ischemia/Reperfusion Injury

Abstract: Background-Despite the importance of endothelial function for coronary regulation, there is little information and virtually no consensus about the causal mechanisms of endothelial dysfunction in myocardial ischemia/reperfusion (I/R) injury. Because tumor necrosis factor-␣ (TNF-␣) is reportedly expressed during ischemia and can induce vascular inflammation leading to endothelial dysfunction, we hypothesized that this inflammatory cytokine may play a pivotal role in I/R injury-induced coronary endothelial dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
131
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 29 publications
6
131
0
4
Order By: Relevance
“…Tumor ne- crosis factor-␣ also induces coronary endothelial dysfunction, which may further diminish coronary flow. 32 Other circulating factors (complement, procalcitonin, neopterin, C-reactive protein, and others) have been reported to contribute to SIRS in CS. Despite a promising randomized phase 2 study, a trial of complement (C5) inhibition in patients with MI found that pexelizumab did not reduce the development of shock or mortality.…”
Section: Peripheral Vasculature Neurohormones and Inflammationmentioning
confidence: 99%
“…Tumor ne- crosis factor-␣ also induces coronary endothelial dysfunction, which may further diminish coronary flow. 32 Other circulating factors (complement, procalcitonin, neopterin, C-reactive protein, and others) have been reported to contribute to SIRS in CS. Despite a promising randomized phase 2 study, a trial of complement (C5) inhibition in patients with MI found that pexelizumab did not reduce the development of shock or mortality.…”
Section: Peripheral Vasculature Neurohormones and Inflammationmentioning
confidence: 99%
“…Other than reoxygenation of ischaemic tissue during reperfusion, activation of NADPH oxidase also significantly contributes to TNF-α-mediated overproduction of O2 .-in vasculature (Chen et al, 2011;Gao et al, 2008;Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence has accumulated that I/R produces vascular endothelial dysfunction as defined by abrogated endothelium-dependent dilation. [1][2][3][4] Moreover, the arterial endothelial nitric oxide synthase (eNOS) protein expression is severely reduced after I/R injury. 3 Given the well-known role of nitric oxide (NO) not only as a vasodilator but also as an inhibitor of neutrophil adhesion and platelet aggregation, [5][6][7] the amelioration of the endothelial dysfunction associated with I/R through the maintenance of an adequate level of eNOS could be important.…”
mentioning
confidence: 99%
“…Reactive oxygen/nitrogen species (ROS/RNS) generation on reperfusion is also generally accepted as a contributing factor to I/R-induced vascular injury. 2 Superoxide and NO can react to the powerful oxidant and nitrating agent peroxynitrite (ONOO À ), reducing the bioavailability of NO and thus resulting in vascular dysfunction. 8 Nitration of functional proteins further contributes to cellular injury, thus suggesting that oxygen radical formation acts as a triggering mechanism for endothelial dysfunction.…”
mentioning
confidence: 99%